(untitled) - Cheney, Lynne V.; Preiss-Glasser, Robin (New York, 2003)
Each letter of the alphabet is represented by an important woman in the history of the United States, as well as others in her same field of accomplishment.
Keywords: Alphabet; Biography; Women; Juvenile literature; Alphabet books; United States; Biography; Women; United States; Biography; United States; History